Strategi Supervisi Berbasis Teknologi dalam Pendidikan Modern - Abdul Rahman Bintang; Restu Permohonan Hasibuan; uhammad Fadel; Ahmad Sabri; Yusran Lubis (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The implementation of technology in educational supervision is an important step to improve the quality of education and the effectiveness of managing the teaching and learning process. The purpose of this study is to analyze how technology-based supervision strategies can be effectively implemented in an educational environment, by reviewing the extent to which technology can improve the quality of teaching and learning. This research uses the literature study method to analyze technology-based supervision strategies in modern education. The desk study was conducted by collecting and reviewing various literatures from scientific journals, books, articles and research reports relevant to the topic. These sources were obtained from reputable academic databases such as Google Scholar, JSTOR, and ProQuest, as well as credible educational websites. The results of this study show that the implementation of technology in educational supervision has been shown to improve effectiveness through increased accuracy, transparency and efficiency in data collection and analysis. Digital tools allow supervisors to provide prompt feedback to teachers and improve collaboration between supervisors, principals and teachers, creating a more integrated learning environment. However, challenges such as lack of technical skills and resistance to change can hinder this process. Therefore, top management support, adequate training and proper infrastructure are essential to optimize the use of technology in educational supervision, so that the overall quality of education can be improved.